Porcine Plasmacytoid Dendritic Cells Are Unique in Their Expression of a Functional NKp46 Receptor - Mair, Kerstin H.; Stadler, Maria; Razavi, Mahsa Adib; Saalmüller, Armin; Gerner, Wilhelm (Frontiers in Immunology, 2022)
The activating receptor NKp46 shows a unique expression pattern on porcine leukocytes. We showed already that in swine not all NK cells express NKp46 and that CD3+NKp46+ lymphocytes form a T-cell subset with unique functional properties. Here we demonstrate the expression of NKp46 on CD4highCD14-CD172a+ porcine plasmacytoid dendritic cells (pDCs). Multicolor flow cytometry analyses revealed that the vast majority of porcine pDCs (94.2% ± 4) express NKp46 ex vivo and have an increased expression on the single-cell level compared to NK cells. FSC/SSChighCD4highNKp46+ cells produced high levels of IFN-α after CpG ODN 2216 stimulation, a hallmark of pDC function. Following receptor triggering with plate-bound monoclonal antibodies against NKp46, phosphorylation of signaling molecules downstream of NKp46 was analyzed in pDCs and NK cells. Comparable to NK cells, NKp46 triggering led to an upregulation of the phosphorylated ribosomal protein S6 (pS6) in pDCs, indicating an active signaling pathway of NKp46 in porcine pDCs. Nevertheless, a defined effector function of the NK-associated receptor on porcine pDCs could not be demonstrated yet. NKp46-mediated cytotoxicity, as shown for NK cells, does not seem to occur, as NKp46+ pDCs did not express perforin. Yet, NKp46 triggering seems to contribute to cytokine production in porcine pDCs, as induction of TNF-α was observed in a small pDC subset after NKp46 cross-linking. To our knowledge, this is the first report on NKp46 expression on pDCs in a mammalian species, showing that this receptor contributes to pDC activation and function.